1976
DOI: 10.1161/01.res.38.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of the natriuretic factor derived from kidney tissue of volume-expanded rats. Effects on short-circuit current and sodium-potassium-adenosine triphosphatase activity.

Abstract: SUMMARY Boiled homogenates of kidneys from volume-expanded and hydropenic rats were subjected Co column chroniatography. The fraction eluting within the range of partition coefficients (K av ) 0.76-0.89 (fraction III) was lyophilized and the effects of this semipurified preparation were assessed on short-circuit current (SCC) across isolated frog skin, on rat kidney cortex Na-K-ATPase activity, and on sodium excretion by the rat in vivo. At a dose of 500 ftg/ml, fraction III from expanded rat kidney inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…In distinction from digoxin or ouabain, the endogenous CTS described by Hillyard et al (1976) did have an appreciable effect on renal Na + /K + -ATPase activity. Work from our laboratories has demonstrated that MBG has potent effects on rat renal Na + /K + -ATPase activity, which can be reversed in vivo by administration of anti-MBG antibodies.…”
Section: Effects Of Endogenous Cardiotonic Steroids On Kidney Andmentioning
confidence: 83%
“…In distinction from digoxin or ouabain, the endogenous CTS described by Hillyard et al (1976) did have an appreciable effect on renal Na + /K + -ATPase activity. Work from our laboratories has demonstrated that MBG has potent effects on rat renal Na + /K + -ATPase activity, which can be reversed in vivo by administration of anti-MBG antibodies.…”
Section: Effects Of Endogenous Cardiotonic Steroids On Kidney Andmentioning
confidence: 83%
“…Before identification of individual CTS in the mammalian tissues, it had been demonstrated that the endogenous CTS are capable of substantially inhibiting renal Na/K-ATPase activity [47]. Three potential mechanisms may be offered to describe how low nanomolar or subnanomolar concentrations of CTS present in mammalian plasma promote natriuresis via interaction with renotubular Na/K-ATPase.…”
Section: Cardiotonic Steroids and Regulation Of Sodium Excretionmentioning
confidence: 99%
“…The present study was designed to investigate in the rat the effect of acute extracellular volume expansion and sodium intake on 385 0143-522 1/80/0503859731.50/1 the amount of this inhibitor which could be extracted from kidney tissue. The work was done (a) to confirm the previous observation by Gonick & Saldanha (1975) and by Hillgard, Lu & Gonick (1976) that natriuretic material can be extracted from the kidney tissue after such a stimulus, and (b) to estimate the influence of the sodium content of the diet on the degree of activity of the natriuretic factor in non-expanded and acutely volume-expanded animals.…”
Section: Introductionmentioning
confidence: 82%